TI_GERICHTE 15.2013.75 vom 8. Oktober 2013 , Verbale di ritenzione degli oggetti colpiti da diritto di ritenzione - TI Tribunale d'appello (2013)
Verbale di ritenzione degli oggetti colpiti da diritto di ritenzione